Saving for Old Age - Demirguc-Kunt, Asli; Klapper, Leora; Panos, Georgios A. (World Bank, Washington, DC, 2016)
Countries around the world face a retirement crisis brought on by aging populations, declining birthrates, and fiscal shortfalls. As a result, policy makers increasingly seek to understand retirement savings patterns, a crucial component of the safety net for the elderly. Drawing on the 2014 Global Findex database, which provides individual-level data on the use of financial products in more than 140 countries, this paper examines how adults save for old age. It finds that about 25 percent of adults worldwide save for old age, with rates exceeding 35 percent in high-income Organisation for Economic Co-operation and Development economies and the East Asia and Pacific region. On average, men are slightly more likely than women to save for this purpose, but the gender gap is deeper in developing countries. Worldwide, saving for old age is more common among older adults, more educated adults, and adults who own accounts. Adults in countries with English legal origin, and with high savings rates, are also more likely to save for old age. The paper also finds that measures to increase trust in the financial system, such as the safety net/moral hazard index based on deposit insurance, lead to higher rates of saving for old age. Finally, the paper finds little evidence of substitution between pension system provisions and contribution rates with saving for old age.